Use of Tissue-Glue–Coated Collagen Sponge (TachoSil) to Repair Minor Cerebral Dural Venous Sinus Lacerations: Technical Note. Issue 1 (12th January 2015) - Gazzeri, Roberto; Galarza, Marcelo; Fiore, Claudio; Callovini, Giorgio; Alfieri, Alex
Abstract: BACKGROUND: Significant hemorrhage may occur from the cerebral venous sinuses during the dural separation from the bone flap, particularly in elderly patients. It is important to achieve an urgent hemostatic control. OBJECTIVE: To evaluate the efficacy and safety of a new fixed combination tissue sealant (TachoSil) in patients with bleeding from lacerations of cerebral venous sinuses. METHODS: Between September 2012 and June 2014, 57 patients (39 female, 18 male) presenting with iatrogenic tears of the superior sagittal or transverse/sigmoid sinuses were treated with a topical fibrin sealant patch. Intraoperative source of bleeding, time to bleeding control, quantity of sealant sponge used, and postoperative complications were evaluated. Time to hemostasis was used as the primary end point. RESULTS: Effective hemostasis, defined as cessation of bleeding after application of topical hemostatic agent, was achieved no later than 4 minutes in all except 5 patients with persistent bleeding from the sinus. In these 5 cases, bleeding was finally stopped after application of a new larger layer of TachoSil Sponge (2 cases) or gelatin hemostatic matrix (2 cases) or fibrin glue (1 case) over the layer of TachoSil. CONCLUSION: We report our experience with a new hemostasis technique to manage bleeding from iatrogenic lacerations of cerebral venous sinuses.